An Inverse Boundary Value Problem for a Semilinear Wave Equation on Lorentzian Manifolds. (11th May 2021) - Hintz, Peter; Uhlmann, Gunther; Zhai, Jian
Abstract: We consider an inverse boundary value problem for a semilinear wave equation on a time-dependent Lorentzian manifold with time-like boundary. The time-dependent coefficients of the nonlinear terms can be recovered in the interior from the knowledge of the Neumann-to-Dirichlet map. Either distorted plane waves or Gaussian beams can be used to derive uniqueness.